Case Study: Theoretical and Practical Learning Achievement in Animal Subcutaneous Injection of Students in Animal Science Program Faculty of Food and Agricultural Technology Pibulsongkram Rajabhat University - Moonsan, Preecha; Inthong, Weerapong (Journal of Mahanakorn Veterinary Medicine, 2018)
The objectives of this research were: 1) to measure the theoretical and practical learning achievement of the students who learned by an integration technique of lecture, demonstration and practice, in animal subcutaneous injection and 2) to measure the satisfaction level of the students on the integration technique of learning. The sample group was specified in 29 sophomore students in Animal Science program in Faculty of Food and Agricultural Technology Pibulsongkram Rajabhat University, who enrolled in the animal hygiene and sanitation subject. The one group pre test-post test design was used for this research. The research tools were the studying document for animal subcutaneous injection, the theoretical and practical learning achievement questionnaire and the learning satisfaction questionnaire. The statistics used for data analysis were percentage, mean, standard deviation and Students t-Test. The result showed that the post-test average learning achievement score of the student (28.52 ± 1.47 points) was higher than the pre-test score (11.00± 0.45 points) (P<0.01). The learning achievement in both the theoretically section and the practical section (8.83 ± 0.66 and 19.67 ± 1.20 points, respectively) were higher than the anticipated standard score at 80% (P<0.01). The overall satisfaction of the students on this technique was high (4.14 ± 0.66 points). These results suggested that the integration technique of lecture, demonstration and practice effectively improved learning achievement.